Signaling Quality through Prices in an Oligopoly - Maarten C.W. Janssen; Santanu Roy (Tinbergen Institute, 2007)
Firms signal high quality through high prices even if the market structure is highly competitive and price competition is severe. In a symmetric Bertrand oligopoly where products may differ only in their quality, production cost is increasing in quality and the quality of each firm's product is private information (not known to consumers or to other firms), we show that there exist fully revealing equilibria in mixed strategies. In such equilibria, low quality firms enjoy market power when other firms are of high quality. High quality firms charge higher prices than low quality firms but lose business to rival firms with higher probability. Some of the revealing equilibria involve high degree of market power (price close to full information monopoly level) while others are more “competitive”. Under certain conditions, if the number of firms is large enough, information is revealed in every equilibrium.
Keywords: L13; L15; D82; D43; 330; Signaling; Quality; Oligopoly; Incomplete Information; Signalling; Produktqualität; Preismanagement; Preiswettbewerb; Oligopol; Unvollkommene Information; Theorie